(3eONd ddJMdjd GdfbOjs - (3eMehO(B, (3MejOGJs ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2000)
(3GdfbO hGdEFJeGf hCSYGQ GdaGFOI,CSYGQ GdUQa,SjGSI CSYGQ GdUQa,GdfXGe GdeUQaj GdLRGFQj,fXGe GdUQa aj GdLRGFQ,fXGe GdQbGHI Ydi GdUQa aj GdLRGFQ(B.s
(3GdeQGLY U(B.213 (3GdLOGhd U(B. 195s
Keywords: (3GdfbhOs